2012
DOI: 10.1007/s00198-012-1895-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in postmenopausal Chinese women treated with calcium fortification in soymilk and cow's milk

Abstract: Daily consumption of milk containing 250 mg calcium over 18 months prevents BMD loss at the hip and the femoral neck in postmenopausal Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 38 publications
0
39
0
2
Order By: Relevance
“…Similar effects of calcium and/or vitamin D fortified milk on bone parameters have been observed in Asian populations. A 16-weeks calcium or calcium/ vitamin D fortified milk trial in post-menopausal Asian women demonstrated reductions in PTH and bone turnover of about 10% and ≥ 20% respectively [25,26]. Two longer term intervention studies with a duration between 18 and 30 months using vitamin D fortified dairy with or without calcium have shown beneficial effects on bone turnover and/or total and site-specific BMD in postmenopausal women [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of calcium and/or vitamin D fortified milk on bone parameters have been observed in Asian populations. A 16-weeks calcium or calcium/ vitamin D fortified milk trial in post-menopausal Asian women demonstrated reductions in PTH and bone turnover of about 10% and ≥ 20% respectively [25,26]. Two longer term intervention studies with a duration between 18 and 30 months using vitamin D fortified dairy with or without calcium have shown beneficial effects on bone turnover and/or total and site-specific BMD in postmenopausal women [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of as low as 500 mg of calcium could effectively slow lumbar spine bone loss in Japanese perimenopausal women with low calcium intake [Nakamura et al, ]. Similar beneficial effects have been observed in postmenopausal women from Hong Kong [Lau et al, ; Haines et al, ; Lee et al, ; Lau et al, ; Ho et al, ], China [Gui et al, ], Chile [Rodriguez and Novik, ], Argentina [Malpeli et al, ] and Nigeria [Umaretiya et al, ]. Interestingly, however, calcium supplementation failed to produce consistent effects on BMD in studies from calcium sufficient areas [Aloia et al, ; Chevalley et al, ; Barger‐Lux et al, ].…”
Section: Implications In Global Health Perspectives – Fracture and Camentioning
confidence: 90%
“…1 Low calcium intake has been associated with lower bone density in some cross-sectional studies, [4][5][6] though not all. 7 Interventions to increase calcium intake in postmenopausal women have shown beneficial effects on bone density, [8][9][10] though in some studies the benefit Gastrointestinal complaints are common with calcium supplements and can be mitigated with osmotic cathartics (mixed in the same pill or not) or with dose adjustment.…”
Section: ■ Calcium Intake and Bone Densitymentioning
confidence: 99%